Electrodissolution processes : fundamentals and applications - Datta, Madhav (Boca Raton : CRC Press, 2021)
"Electrodissolution Processes: Fundamentals and Applications discusses the basic principles involved in high rate anodic dissolution processes and their application in advanced machining, micromachining, and finishing operations. The fundamental section of the book discusses the anodic dissolution behavior of different classes of metals and the influence of mass-transport, current distribution, and surface film properties on the metal removal rate and surface finishing. The application section of the book presents essential elements of electrochemical and assisted techniques for precision machining, micromachining, and polishing of advanced materials including hard to machine conducting ceramic materials. Salient features of the book: A first-of-its-kind book which provides the reader with an updated scientific and engineering information related to high rate anodic dissolution processes. Highlights the importance of the understanding of basic principles required for designing and optimization of ECM/EMM/EP processes. Gives equal emphasis on the fundamentals and the applications of electrodissolution processes Discusses the high rate andic dissolution of two broad classes of materials namely engineering and refractory materials. Presents case studies to demonstrate the capabilities of different electrochemical and assisted machining, micromachining, and finishing operations. Presents a dedicated chapter on electrochemical planarization of copper interconnects"--
OCLC-licensed vendor bibliographic record.
Keywords: Electrochemical cutting; Dissolution (Chemistry); Electrocatalysis; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Industrial Design / General